Steady and transient simulation results of air injection into aeroderivative gas turbines for power augmentation and ramp rate improvement - Abudu, Kamal (Cranfield University, 2020)
The data set includes Turbomatch results for the steady state and transient injection of air into two aeroderivative engines. The engines considered are inspired by the GE LM6000(TS56) and LMS100(TSI118). The steady state simulations data provides engine design specifications and the effect of increased injection on the engines' performance. A ramp up stimulation from 50% of power to full load is also provided for both engines.
Keywords: Aeroderivative gas turbines; Ramp rates; Flexibility; Transient GT Simulation; LM6000; LMS100; Energy Generation; Conversion and Storage Engineering